Advances in Technologies for Highly Active Omega-3 Fatty Acids from Krill Oil: Clinical Applications - Alessandro Colletti; Giancarlo Cravotto; Valentina Citi; Alma Martelli; Lara Testai; Arrigo F. G. Cicero (Marine Drugs, 2021)
Euphausia superba, commonly known as krill, is a small marine crustacean from the Antarctic Ocean that plays an important role in the marine ecosystem, serving as feed for most fish. It is a known source of highly bioavailable omega-3 polyunsaturated fatty acids (eicosapentaenoic acid and docosahexaenoic acid). In preclinical studies, krill oil showed metabolic, anti-inflammatory, neuroprotective and chemo preventive effects, while in clinical trials it showed significant metabolic, vascular and ergogenic actions. Solvent extraction is the most conventional method to obtain krill oil. However, different solvents must be used to extract all lipids from krill because of the diversity of the polarities of the lipid compounds in the biomass. This review aims to provide an overview of the chemical composition, bioavailability and bioaccessibility of krill oil, as well as the mechanisms of action, classic and non-conventional extraction techniques, health benefits and current applications of this marine crustacean.